Staging Habla de negros : radical performances of the African diaspora in early modern Spain - Jones, Nicholas R., 1982- (University Park, Pennsylvania : The Pennsylvania State University Press, 2019)
"In this volume, Nicholas R. Jones analyzes white appropriations of black African voices in Spanish theater from the 1500s through the 1700s, when the performance of Africanized Castilian, commonly referred to as habla de negros (black speech), was in vogue.Focusing on Spanish Golden Age theater and performative poetry from authors such as Calderón de la Barca, Lope de Rueda, and Rodrigo de Reinosa, Jones makes a strong case for revising the belief, long held by literary critics and linguists, that white appropriations and representations of habla de negros language are "racist buffoonery" or stereotype. Instead, Jones shows black characters who laugh, sing, and shout, ultimately combating the violent desire of white supremacy. By placing early modern Iberia in conversation with discourses on African diaspora studies, Jones showcases how black Africans and their descendants who built communities in early modern Spain were rendered legible in performative literary texts.Accessibly written and theoretically sophisticated, Jones's groundbreaking study elucidates the ways that habla de negros animated black Africans'agency, empowered their resistance, and highlighted their African cultural retentions. This must-read book on identity building, performance, and race will captivate audiences across disciplines."--
Introduction : the habla de negros palimpsest, theorizing habla de negros -- Black skin acts : feasting on blackness, staging linguistic blackface -- The birth of hispanic habla de negros : signifying for the black audience in Rodrigo de Reinosa -- Black divas, black feminisms : the black female body and habla de negros in Lope de Rueda -- Afterword : b(l)ack to the future; the postmodern legacy of habla de negros, or talking in tongues.
Includes bibliographical references (pages 165-212) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Theater -- Spain -- African influences -- History -- 16th century; Theater -- Spain -- African influences -- History -- 17th century; Theater -- Spain -- African influences -- History -- 18th century; African diaspora in literature; Performing arts; Théâtre -- Espagne -- Influence africaine -- Histoire -- 16e siècle.; Théâtre -- Espagne -- Influence africaine -- Histoire -- 17e siècle.; Théâtre -- Espagne -- Influence africaine -- Histoire -- 18e siècle.; Africains -- Pays étrangers, dans la littérature.; Arts du spectacle; performing arts (discipline); PERFORMING ARTS -- Theater -- General; African diaspora in literature; Spain; 1500-1799; History